Small Blubber Samples (50 mg) Sufficient for Analyses of 10 Stress and Reproductive Steroid Hormones in Gray and Fin Whales via Liquid Chromatography Mass Spectrometry - Wittmaack, Christiana; Urbán Ramírez, Jorge; Bernot-Simon, Daniela; Martínez-Aguilar, Sergio; Subbiah, Seenivasan; Surles, James G.; Looney, Mary; Kumar, Naveen; Halaska, Barbie; Duignan, Pádraig J.; Knauss, Madelyn; Burns, Kristen; et al. (Frontiers in Marine Science, 2022)
Information on stress, reproductive fitness, and health is difficult to obtain in wild cetaceans but critical for conservation and management. The goal of this study was to develop a methodology requiring minimal blubber mass for analysis of reproductive and stress steroid hormones and, hence, suitable for cetacean biopsies. Blubber biopsies and samples were collected from free-ranging and stranded gray and fin whales. Steroid hormones were extracted from masses as small as 50mg using liquid-liquid extraction methodology developed to handle the high fat content of blubber. Samples were analyzed via liquid chromatography with tandem mass spectrometry for ten hormones: aldosterone, androstenedione, cortisol, cortisone, corticosterone, 17ß-estradiol, estrone, 17α-hydroxyprogesterone, progesterone, and testosterone. As part of the optimization, homogenization via bead beating and blade dispersion were compared, and the former found superior. To investigate optimal yet minimal tissue mass required, hormone panels were compared among paired 50mg, 150mg, and 400mg samples, the latter two being commonly reported masses for hormone blubber analysis. Results indicated that 50mg of blubber was suitable and sometimes superior. Additionally, significant differences in precision values were observed between species, possibly stemming from differences in blubber composition, and relevant to homogenization technique selection and matrix match calibrations. Finally, we identified significant differences in corticosteroid concentrations between stranded and free ranging animals. We present a robust methodology for the analysis of multiple reproductive and stress steroid hormones in minimal masses of cetacean blubber compatible with small biopsies and propose threshold values for stress identification.